ANALISIS PERILAKU EFIKASI KOLEKTIF PADA MASYARAKAT KAMPUNG DESAIN - Kusuma, Patria Jati; Yuwono, Susatyo; Heleconia, Violytha (Program Studi S1 Psikologi, 2024)
The way to overcome crime, and increase the economic productivity of the community is to empower the potential that is owned by the community itself. This potential is developed together so that it creates confidence to be able to move forward and develop together which is called collective efficacy. The purpose of this study is to analyze and explore in depth about collective efficacy behavior. The specific target in this study is the collective efficacy behavior carried out by the Kaliabu Village community which is able to increase their economic productivity. The research method used is qualitative with a case study approach. The data collection method used in this study was interviewing seven informants with the main job criteria as logo designers, as pioneers of the collective efficacy process and as figures who could drive the collective efficacy process to increase the productivity of the people of Kaliabu Village. The results of this research are the first to state that the factors that influence collective efficacy are environmental factors and economic factors. Second, the forms and benefits of collective efficacy are obtained. Keywords: Efikasi kolektif, Graphic / Logo Design, Design Village